Pembelajaran Blended Learning dengan Metode Praktikum untuk Meningkatkan Hasil Belajar Fisika Siswa SMK - Herma Yunita; Feriansyah Sesunan; Hervin Maulina; Wayan Suana (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
The Covid-19 pandemic and government regulations regarding the Enforcement of Restrictions on Community Activities in Indonesia have caused face-to-face learning activities not to be fully implemented. One way to be used as an alternative is through blended learning, which combines online and offline learning activities. This study aims to test vocational students' learning outcomes through blended learning with practicum methods. The population of this study was all students of class XI TKJ of SMK Negeri 1 Liwa, and the samples selected by purposive sampling technique were students of class X-TKJ1 as the control class and students of X-TKJ2 as the experimental class. This study used a pretest-posttest control group design. The two sample classes were given a pretest and posttest, which were then analyzed to determine the N-gain for each class. The results showed differences in student learning outcomes in the experimental and control classes with N-gains, respectively, 0.72 and 0.40. The analysis results showed that the average increase in student learning outcomes in the experimental class was higher than in the control class. Based on the results of data analysis, it can be concluded that blended learning with practicum methods can improve student learning outcomes.